Penerapan Knowledge Management System pada E-Learning dengan Metode COLLES Untuk meningkatkan hasil belajar siswa - Yusnia Budiarti - STMIK Nusa Mandiri Jakarta (Universitas Bina Sarana Informatika, 2015)
ABSTRACT - Knowledge Management in this time become an important system to be applied by organizational company and in order to improving Competitive Advantage and manage company or organisation asset having the character of it’s intellectual. Important of management of good management knowledge is way of to obtain; get knowledge and also way of the transfer of knowledge, becoming attention from Primagama.Primagama is a tuition institute learn owning duty develop study materials and items for educative student of. Existence of demarcation of time for the process of study in class grow to feel unsatisfaction to student to share knowledge among the other student and also with teacher. In this research the problem of study related to Knowledge Management exploiting maximally will be found by correct solution so that in the end can quicken process of its transfer of knowledge, creation of study items development innovation and knowledge use 10 step roadmap method of KMS.In this research will be made by Knowledge Management System able to be exploited to support application exploiting and implementation of make-up the study process, used application by being based on Learning Management System (LMS) Moodle and Constructivist Online Learning Environment Survey method (COLLES) to test freshment usage of Learning e-smart application. Key words : Development Prototype, Knowledge Management System, COLLES Method